Understanding entrepreneurial success: A phenomenographic approach. (September 2018) - Angel, Pablo; Jenkins, Anna; Stephens, Anna
Entrepreneurship research has predominately focused on firm-level conceptions of success and the personal factors that help predict them but has stopped short of investigating what it means to entrepreneurs. When entrepreneurial success has been studied at the individual level, the approach has been to identify common success criteria and examine the importance of these to the entrepreneur. However, criteria-based approaches overlook the possibility that entrepreneurs may ascribe different meanings to common success criteria, and this can influence how entrepreneurs develop their firms. In this article, we adopt a phenomenographic approach to explore what success means to entrepreneurs. Our analysis reveals four qualitatively distinct understandings of entrepreneurial success and shows that entrepreneurs interpret common success criteria differently depending on their underlying understanding of success. These findings extend the literature on entrepreneurial success by illustrating that entrepreneurs not only vary in the importance they place on different success criteria but also vary in how they understand these different success criteria.